Social analytics and the digital economy in the context of global communication and the challenges of the information society - Yaskevich, Yadwiga S. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article reveals the status and purpose of social analytics and the digital economy in the context of global social communication and the challenges of the information society. It is shown that a timely education system receives today a social order for the training of specialists who are able to work in a modern network space, possessing interdisciplinary knowledge, able to combine organizational and managerial abilities, technological skills and creativity.
Keywords: social media analytics; global social communication; information society; media business; social analytics; management; university education; digital economy